1981
DOI: 10.1002/art.1780241001
|View full text |Cite
|
Sign up to set email alerts
|

Decreased capacity to solubilize immune complexes in sera from patients with systemic lupus erythematosus

Abstract: The capacity to solubilize immune complexes formed in vitro is significantly decreased in patients with systemic lupus erythematosus (SLE). This complement function correlates significantly with serum C3 levels and inversely with the presence of circulating immune complexes. Clinically, patients with a decreased capacity to solubilize complexes show a worse evolution and an increased incidence of renal involvement. In conclusion, the impaired solubilization capacity, related to low complement activity, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1982
1982
1985
1985

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 13 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…Preliminary studies have shown that impairment of these functions correlated equally well with disease activity and with complement component levels in patients with systemic lupus erythematosus, vasculitis, or post-streptocaccal glomerulonephritis (7)(8)(9).…”
mentioning
confidence: 99%
“…Preliminary studies have shown that impairment of these functions correlated equally well with disease activity and with complement component levels in patients with systemic lupus erythematosus, vasculitis, or post-streptocaccal glomerulonephritis (7)(8)(9).…”
mentioning
confidence: 99%
“…A decrease in the capacity to solubilize complexes observed in sera from patients with systemic lupus erythematosus (Aguado et al 1981) might be additively contributing to the immune complex deposition in various tissues in this disease (Kofer et al 1967;Miescher et al 1976). …”
Section: Discussionmentioning
confidence: 99%
“…Studies of CMS in sera from patients with IC disease have mainly focused upon SLE [2,5,6,9,65,68], In these reports the CMS capacity was found reduced below the nor mal reference range in a large fraction of these sera ( fig. 2).…”
Section: Interaction Of C-solubilized Immune Complexes With C3 Receptorsmentioning
confidence: 99%
“…These data indicate that no single factor is responsible for the diminished capacity of SLE sera to solubilize IC, but low concentrations of one or more factors in the classical or alternative pathway may contrib ute to the reduced CMS. Furthermore, there appears to be no simple association between solubilization capacity and CIC levels in SLE patients [2,7,68].…”
Section: Solubilization Of Immune Complexes By Patient Seramentioning
confidence: 99%